Phenolics and Antioxidant Activity of Mushroom Leucopaxillus giganteus Mycelium at Different Carbon Sources - Barros, Lillian (2008)
This article reports the first approach to the antioxidant potential evaluation of the edible mushroom Leucopaxillus giganteus mycelium obtained in the presence of four different carbon sources: glucose, sucrose, fructose and mannitol. Despite the use of Leucopaxillus mushroom species in chemical industry for extraction of clitocybin antibiotic, the production of its mycelium for pharmacological applications has not been explored. The concentration of antioxidant compounds increased along the growth time as a response to the oxidative stress and therefore free radicals production. The aldohexose glucose proved to be the most appropriate carbon source to increase antioxidant activity, leading to the highest phenols content and lowest EC50 values. Significant negative linear regressions were established between phenols and flavonoids contents, and antioxidant activity, which support that the extracts mechanism of action for the different antioxidant activity assays may be identical, being related with the content in those compounds and their free radical scavenging activity.